The Changing Situation of Labor Market Entrants in Germany: A Long-Run Analysis of Wages and Occupational Patterns - Mario Reinhold; Stephan L. Thomsen (Institute for the Study of Labor (IZA), 2016)
Concurrently with a steady increase of the supply of college educated workers, recent evidence for the U.S. indicated a decline in the demand for and the real wages of this group after 2000. We investigate empirically, whether there has been a similar trend in Germany. Based on comprehensive, long-run administrative data for the years 1975 to 2010, we use a set of employment indicators to analyze labor market patterns of job market entrants. Besides consideration of the developments of education attainment and wages over time, we put a particular focus on changes of the task composition, the chances of entering top-paying jobs, entry wages and wage growth, and skill premia over time. To allow for a detailed analysis, we distinguish four education groups. The empirical picture shows that since the year 2000 job entrants with higher education have experienced decreasing employment shares in top-paying positions. Moreover, starting wages and wage growth have both decreased, too. A reason for this has been the substitution of jobs that were formerly executed by lower qualifications. Our findings reveal similarities between Germany and the U.S. in terms of some declining fortunes of the young. However, whereas in the U.S. college educated workers have been affected, the results indicate that in Germany the medium-skilled and low-skilled have been particularly impaired.
Keywords: J21; J23; J24; 330; labor demand; labor supply; occupational sorting; wages; education groups